2018
DOI: 10.1007/978-1-4939-8594-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Endophytes in Plant Tissue Culture: Mode of Action, Detection, and Control

Abstract: Endophytic bacteria have been increasingly in the focus of research projects during the last decade. This has changed the view on bacteria in plant tissue culture and led to the differentiation between artificially introduced contaminations and naturally occurring endophytes with neutral, negative, or positive impact on the plant propagation process. This review chapter gives an overview on recent findings about the impact that bacteria have on the plant physiology in general and during micropropagation. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 102 publications
0
15
0
Order By: Relevance
“…microbial growth , measured as observable growth of either bacterial or fungal organisms associated to plant tissue, potentially attributable to possible endophyte overgrowth (W T N = 75, W N = 75, D N = 75, D T = 75). In accordance with Quambusch & Winkelmann (2018), we only considered as possible endophytes those microorganisms growing directly on the explant, not in the culture media;…”
Section: Methodsmentioning
confidence: 99%
“…microbial growth , measured as observable growth of either bacterial or fungal organisms associated to plant tissue, potentially attributable to possible endophyte overgrowth (W T N = 75, W N = 75, D N = 75, D T = 75). In accordance with Quambusch & Winkelmann (2018), we only considered as possible endophytes those microorganisms growing directly on the explant, not in the culture media;…”
Section: Methodsmentioning
confidence: 99%
“…Endophytic bacteria, such as B. subtilis , can protect plants by producing antibiotics that inhibit pathogen development and promote induced systemic resistance (ISR) [ 31 ]. Inoculation of endophyte microorganisms during micropropagation is an alternative that can improve crop quality and increase the content of specialized metabolites such as flavonoids and phenolic compounds in general [ 25 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few years later, Elmeskaoui et al (1995) have shown that biotized plant tissue cultures benefit from microbial presence through an improvement in photosynthetic efficiency and biomass production. Generally, PGPB improve growth by releasing PGRs required for vitropropagation (Quambusch and Winkelmann, 2018). Auxins and cytokinins biosynthesis are widespread among rhizobacteria, and different biosynthesis pathways have been identified (Kado, 1984;Amara et al, 2015).…”
Section: Beneficial Effects Of Plant Growth Promoting Bacteria In In mentioning
confidence: 99%